2012
DOI: 10.1038/srep00723
|View full text |Cite
|
Sign up to set email alerts
|

A New Metrics for Countries' Fitness and Products' Complexity

Abstract: Classical economic theories prescribe specialization of countries industrial production. Inspection of the country databases of exported products shows that this is not the case: successful countries are extremely diversified, in analogy with biosystems evolving in a competitive dynamical environment. The challenge is assessing quantitatively the non-monetary competitive advantage of diversification which represents the hidden potential for development and growth. Here we develop a new statistical approach bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
800
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 451 publications
(833 citation statements)
references
References 17 publications
22
800
1
10
Order By: Relevance
“…For example, its original implementation in physics was designed to obtain a unified and consistent picture of a microscopic world (made up of molecules and atoms obeying the time-reversible Newton mechanics) with a macroscopic world (obeying the phenomenological rules of thermodynamics, where time reversibility is lost and whose evolution is described in terms of mean values and fluctuations). Nowadays, statistical mechanics has been used successfully in several fields of research, ranging from chemistry (Agliari et al, 2015) and biology (Buchanan, 2010) to sociology (Durlauf, 1999), finance (Bouchaud and Potters, 2009) and economics (Tacchella, 2002). Here, the microscopic world is the network of connections between natives and migrants and the macroscopic world is the development and diversification of exports in the territory where natives and migrants live.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, its original implementation in physics was designed to obtain a unified and consistent picture of a microscopic world (made up of molecules and atoms obeying the time-reversible Newton mechanics) with a macroscopic world (obeying the phenomenological rules of thermodynamics, where time reversibility is lost and whose evolution is described in terms of mean values and fluctuations). Nowadays, statistical mechanics has been used successfully in several fields of research, ranging from chemistry (Agliari et al, 2015) and biology (Buchanan, 2010) to sociology (Durlauf, 1999), finance (Bouchaud and Potters, 2009) and economics (Tacchella, 2002). Here, the microscopic world is the network of connections between natives and migrants and the macroscopic world is the development and diversification of exports in the territory where natives and migrants live.…”
Section: Methodsmentioning
confidence: 99%
“…In order to keep the analysis as smooth as possible, we follow the simplest possible route (leaving possible improvements based on, for instance, complexity measures (Tacchella, 2002;Caldarelli and et al, 2012;Cristelli and et al, 2013) as options for future additional work): the export portfolio of a province is composed of products and destinations. That is, a province can export several products to a single destination or export the same product to several destinations.…”
Section: Data Analysis On Export Product Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The countries' future exports are particularly complex to predict, as their evolution depends on many external factors, such as geographical position, diplomatic relations between countries, available natural resources, and technologies. Nevertheless, previous studies [6,13] showed that it is possible to measure the competitiveness of a country, estimate its future growth and even predict its future exports using solely the international trade data. The last aspect, personalized prediction of future exports for each country, further suffers from the lack of a traditional approach with conventional metrics and renowned prediction algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…[13]. The first definition of Economic Complexity was made by the use of two self-consistent linear equations [20,21], which were then successfully applied to predict the long-term growth of countries' export basket.…”
Section: Introductionmentioning
confidence: 99%